The level and determinants of international patient satisfaction with dental tourism in Bangkok, Thailand - Hnin Nu Nu Lwin; Prattana Punnakitikashem; Trin Thananusak (Cogent Business & Management, 2021)
Along with the medical tourism industry, dental tourism has become a trending industry as many patients travel around the world to receive dental treatment. This research aims to analyze the level of international patient satisfaction with the dental tourism experience in Bangkok, and to identify the determinants that significantly influence patient satisfaction. This study applied a cross-sectional research design and a quantitative research method. The data were collected using questionnaires. A total of 106 respondents were involved in this study. Descriptive statistics, correlation and multiple linear regression analyses were performed to address the research objectives of the study. It was found that international patients are highly satisfied with their dental tourism experiences in Bangkok. In addition, the results showed that quality of dental treatment, location accessibility and destination appeal have a positive and significant influence on dental tourist satisfaction. This study provides valuable inputs for dental care providers by highlighting the determinants and their relationships to dental tourist satisfaction to overcome challenges in this competitive market.
Keywords: 650; Dental tourism; dental tourists; patient satisfaction; Bangkok